2003
DOI: 10.1002/ca.10114
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar lordosis: Study of patients with and without low back pain

Abstract: We used magnetic resonance imaging (MRI) to assess lumbar lordosis in 27 patients with low back pain and 19 patients and 10 volunteers with no known back pain. Our study aimed to investigate whether lordosis changes with age and is reduced in those with low back pain. Although our results confirm known observations that lumbar lordosis is more prominent in women (P < 0.01) and those with a higher body mass index (P < 0.04), we were unable to demonstrate any significant variation in lordosis with age. Nor could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
59
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 14 publications
14
59
0
5
Order By: Relevance
“…Overall, our findings for the cervical spine appear to mirror the majority of those reported for the lumbar spine: whilst there is some suggestion that individuals with a flatter spine (reduced lordosis) have a slightly higher risk of developing low back pain [1], the vast majority of cross-sectional studies conclude that there is no significant difference in the degree of lordosis in people with and without back pain [20,36,39].…”
Section: Discussionsupporting
confidence: 76%
“…Overall, our findings for the cervical spine appear to mirror the majority of those reported for the lumbar spine: whilst there is some suggestion that individuals with a flatter spine (reduced lordosis) have a slightly higher risk of developing low back pain [1], the vast majority of cross-sectional studies conclude that there is no significant difference in the degree of lordosis in people with and without back pain [20,36,39].…”
Section: Discussionsupporting
confidence: 76%
“…126 Several other studies have observed the degree of standing lumbar lordosis in the female spine to be 26%-28% greater than the male spine; 30,139,210 however, no information was provided on the parous history of those females. Interestingly, changes in mass distribution in the body due to increased body mass index showed little 85,137 or no effect on lumbar lordosis in males or females.…”
Section: Sexual Dimorphism and The Lumbar Spinementioning
confidence: 95%
“…Some studies found no association between the lordosis and age (Kalichman et al, 2011;Murrie et al, 2003) while others reported age-related decrease (Amonoo-Kuofi, 1992) or increase (Tüzün et al, 1999) in the lordosis. In a preliminary study (not reported here) simulating forward flexion, however, the initial L1-S1 lordosis Cobb's angle was increased by 10 o (from 46 o ) while preserving the kyphosis angle and the sacral plumb line in agreement with the literature (Endo et al, 2010;Jackson et al, 1998;Park et al, 2013).…”
Section: Interpretationsmentioning
confidence: 99%